Pola Komunikasi Organisasi Antara Pemimpin dan Bawahan PT Barat Karya Indonesia Dalam Meningkatkan Produktivitas Kinerja Karyawan: Pola Komunikasi Organisasi - Permana, Muhamad Dovan (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
Research entitled "Organizational Communication Patterns between Leaders and Subordinates of PT. Barat Karya Indonesia in Increasing Employee Performance Productivity" highlights the significance of efficient communication patterns in an organization to achieve the desired productivity. The purpose of this research is to analyze the influence of communication between leaders and subordinates on employee performance at PT. Barat Karya Indonesia. The method applied in this research is a descriptive qualitative approach, which allows researchers to directly observe interactions and communication patterns in an organizational context. Data was obtained through interviews, observation and document analysis. Research findings show that communication patterns in companies include both formal communication, which is carried out through meetings and reports, and informal communication that occurs in daily interactions. Communication from leaders to subordinates has proven to be very influential on employee work motivation, where leaders provide direction and constructive feedback. Apart from that, horizontal communication between employees also contributes significantly to building solid teamwork.